A New Species in the Canthon indigaceus Species Group (Coleoptera: Scarabaeidae: Scarabaeinae) from the Mexican Pacific Coast - Sara Lariza Rivera-Gasperín; Fernando Escobar-Hernández; Lucrecia Arellano (Taxonomy)
The Canthon indigaceus species group represents a Typical Neotropical distributional pattern with wide penetration into the Mexican Transition Zone. This group consists of three species: C. (C.) indigaceus LeConte; C. (C.) chiapas Robinson; and C. (C.) chevrolati Harold. In this study, a new species for the group is described, C. (C.) cuixmala, collected along the tropical region of the Pacific coast and the Balsas River basin. The taxonomic status of members of the group were evaluated by comparing morphological characteristics and their biogeographic distributions. An updated dichotomous key is provided to separate members of this species group.